Physical activities traditional games and javanese culture of particularly Wayang Kulit - Antonius Tri Wibowo; Yustinus Sukarmin; Sugeng Purwanto; Dody Tri Iwandana (H.S. Skovoroda Kharkiv National Pedagogical University, 2023)
Abstract Physical activity has a favorable influence, including teaching students to focus on learning, as well as strengthening emotional control and emotional intelligence. Games that use technology can prevent children from feeling the game's process, from feeling how to cooperate with their peers, from learning to tolerate, understand, and forgive one another, and from inhibiting psychomotor development and cognitive (thinking) and affective (emotional). Purpose This study aims to determine how much interest teenagers have in traditional games and Javanese culture, especially Wayang Kulit in the Special Region of Yogyakarta. Material and methods This research is a survey method, data collection using a questionnaire. The sampling technique used was purposive sampling with the criteria of adolescents aged 13-19 years domiciled in the Province of the Special Region of Yogyakarta totaling 478 consisting of 293 males and 185 females. Results From this study, the results obtained were the variable data of traditional games, the interest factor of teenagers in traditional games with a score of 34,946 in the "high" category, the action factor for playing traditional games with a score of 32,686 in the "medium" category. As for the Javanese culture variable regarding Wayang Kulit, the Javanese cultural interest factor scores 32,686 in the "medium" category and the action factor for Javanese culture scores 22,069 in the "low" category. Conclusions The conclusions in this study are joint effort needed whether parents always introduce Javanese culture and traditional games to their children, teachers introduce them consistently through physical education learning, and the government makes policies that require the introduction of Javanese culture and traditional games to always be carried out regularly. In addition, alternative innovations are needed to develop fun sports games to introduce Javanese culture, especially Wayang Kulit and traditional games so that if they are consistently carried out continuously, Javanese culture and traditional games will remain sustainable.